Immunohistochemical expression of CD10 antigen in uterine adenosarcoma. Issue 6 (1st November 2004) - AMANT, F.; STEENKISTE, E.; SCHURMANS, K.; VERBIST, L.; Abeler, V. M.; TULUNAY, G.; DE JONGE, E.; MASSUGER, L.; MOERMAN, P.; VERGOTE, I.
Abstract : Uterine adenosarcoma (UAS) is microscopically characterized by a biphasic growth pattern. By definition, the epithelial component is benign, whereas the stromal component typically has the appearance of a low-grade sarcoma, usually an endometrial stromal sarcoma. CD10 acts by reducing cellular response to peptide hormones and is currently regarded as a specific marker for endometrial stromal tumors. In this international multicenter study, we further explored CD10 immunoreactivity in 30 UASs. We encountered CD10 positivity of the sarcomatous component in 18/20 (90%) of UASs, in five of eight (63%) of UASs with sarcomatous overgrowth as well as in both cases of recurrent UAS. The epithelial component stained negative in all cases. These findings suggest that CD10 can be used to differentiate UAS from cellular leiomyoma, or in case endometrial stromal cells exhibit muscle differentiation. Furthermore, CD10 positivity in recurrent UAS might guide the pathologist toward an endometrial stromal origin.